2015
DOI: 10.1021/acs.jpcc.5b09903
|View full text |Cite
|
Sign up to set email alerts
|

Fluence Threshold for Photothermal Bubble Generation Using Plasmonic Nanoparticles

Abstract: International audienceUnder nano- to femtosecond pulsed illumination at their plasmonic resonance wavelength, metalnanoparticles efficiently absorb the incident light energy that is subsequently converted into heat. In aliquid environment, with sufficiently high pulse fluences (light energy per unit area), this heat generationmay result in the local formation of a transient nanobubble. This phenomenon has been the subjectof a decade of investigations and is at the basis of numerous applications from cancer the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
246
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(264 citation statements)
references
References 46 publications
(128 reference statements)
10
246
2
6
Order By: Relevance
“…In the NP-water suspension, the laser thermally excites the suspended NPs at the SPR, which leads to volumetric heating of the volume irradiated by the laser beam [22][23][24][25][26] . The volumetric heating induces a thermo-capillary convective flow as schematically shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the NP-water suspension, the laser thermally excites the suspended NPs at the SPR, which leads to volumetric heating of the volume irradiated by the laser beam [22][23][24][25][26] . The volumetric heating induces a thermo-capillary convective flow as schematically shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 shows that some metallic nanodimers present strong phototaxis ( F // = 0). Therefore, illuminated nanodimers such as the AgAg (20,20) (for silversilver symmetrical homodimer of r 1 = r 2 = 20 nm) will not only present thermophoretic forces but they will also exhibit net velocity parallel to the direction of illumination.…”
Section: Resultsmentioning
confidence: 99%
“…Also noteworthy is that the nanodimer's force profile appears to be highly sensitive to Figure 6: Force spectra for symmetrical homodimers (left) and symmetrical heterodimers (right) made of NPs of silver (Ag), gold (Au) and copper (Cu), with r 1 = r 2 = 20 nm and gap = 5 nm. We used the maximum of the force spectrum of AgAg (20,20) to normalize the figures. the material.…”
Section: Homodimers and Heterodimersmentioning
confidence: 99%
“…Heat transfer from NPs to the surrounding liquid induces formation of vapor bubbles around them [48]. It was shown that the threshold of formation of such vapor bubbles is close to the NPs fragmentation threshold and exhibit a "bathtub" profile as a function of the NPs diameter [49]. Therefore, more energy per pulse is required to produce smaller NPs by LFL.…”
Section: Laser Fragmentationmentioning
confidence: 99%